Perlindungan Hukum Bagi Pembeli Dalam Perjanjian Jual Beli Batu Bata Merah di Putra Lio Taktakan Kota Serang - Sulasno Sulasno; Fuqoha Fuqoha; Indriarti Chandra (JURNAL HAK : Kajian Ilmu Hukum, Administrasi Negara, dan Komunikasi, 2023)
Economic and business activities carried out by the parties, especially between sellers and buyers, have not been given maximum legal protection. Phenomena or dynamics in society when carrying out legal relations in the form of buying and selling based on agreements, agreements made by the parties as laws, and the birth of an agreement between the parties, for that they are obliged to make an agreement. The purpose of this research is to find out the implementation of the red brick sale and purchase agreement and to find out the legal settlement methods for the parties in the event of default on the buyer at Putra Lio Takakan, Serang city. This study uses a qualitative method with a sociological juridical approach, the data used are primary, secondary and tertiary data. The results of this study are as follows: In the implementation of the red brick sale and purchase agreement, it is in accordance with the agreement, but in practice there are defaults and efforts to resolve them by means of deliberation, but if there is no consensus between the seller and the buyer, both parties agree to settle through litigation.